2001
DOI: 10.1046/j.1440-1843.2001.00337.x
|View full text |Cite
|
Sign up to set email alerts
|

The brainstem auditory evoked potential abnormalities in severe chronic obstructive pulmonary disease

Abstract: The functions of the eighth cranial nerve and brainstem were highly impaired in severe COPD. These pathological BAEP alterations in severe COPD might be due to the chronic hypoxic-hypercapnic status occurring in the brainstem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 14 publications
2
15
0
Order By: Relevance
“…They have not described the details of the inclusion and irreversibility criteria. Atis et al [5] included 21 patients with severe COPD according to the criteria[15] of the American Thoracic Society (1987). Some of the patients included had clinical evidence of neuropathy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They have not described the details of the inclusion and irreversibility criteria. Atis et al [5] included 21 patients with severe COPD according to the criteria[15] of the American Thoracic Society (1987). Some of the patients included had clinical evidence of neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…[4] Atis and co-workers studied BAEP in patients with severe COPD and concluded that eighth cranial nerve and brainstem functions were impaired in COPD. [5] Barbieri et al reported that there was no significant difference in BAEP in mild-or-moderate chronic respiratory insufficiency, apart from acidosis. [6] It appears the previous studies have included COPD patients having severe airflow obstruction or significant hypoxemia/hypercapnia.…”
mentioning
confidence: 99%
“…In the rat, the acoustic nerve generates peak I, the cochlear nucleus peak II, the superior olivary nucleus peak III, the lateral lemniscus peak IV, and the inferior colliculus peak V (30). Increased interpeak intervals may be an indication of anomalous myelination or nerve conduction as well as brainstem, thalamic, and͞or cortical deficits (31,32). Cochlear and brainstem auditory nuclei are highly sensitive to oxygen shortage (25,33).…”
Section: Discussionmentioning
confidence: 99%
“…Kotterba et al analyzing data relative to 20 patients affected by severe OSAS, found prolongations of wave latency I ( P B 0.001) and interpeak latency I-V (P B 0.001) in the 60 % of the total sample, with 9 (45 %) subjects characterized by pontomesencephal lesions [13]. The auditory pathway sensitiveness to reduced oxygen levels was also investigated by Atiş et al who recorded the ABR of 21 patients with severe chronic obstructive pulmonary disease, with the 76.1 % of the sample showing ABR abnormalities like prolonged wave I peak latencies (42.8 %), wave V peak latencies (38.1 %) and III-V interpeak latencies (38.1 %) [14]. Recently Casale et al comparing audiological data of 18 patients with severe OSAS and 21 simple snoring subjects, evidenced prolonged mean latencies of waves I, III, V (P \ 0.05) and a significantly (P \ 0.01) higher pure-tone audiometry (PTA) in OSAS group with respect to healthy people [15].…”
Section: Introductionmentioning
confidence: 99%